Conjunctival Kaposi’s sarcoma as the initial manifestation of acquired inmunodeficiency syndrome - Rodriguez, Carlos Izquierdo; Cordova, JM (Nepalese Journal of Ophthalmology, 2013)
Introduction: Kaposi’s sarcoma is a common neoplasm in patients with acquired immunodeficiency syndrome (AIDS). Its presentation as an initial manifestation of AIDS is very rare . Objective: To report a rare case with Kaposi’s’s sarcoma as an initial manifestation of AIDS. Case: We report the case of a 37-year-old man who was a parenteral drug addict, HIV seropositive and was not under any treatment with a conjunctival lesion which was diagnosed as Kaposi’s sarcoma after surgical resection. Conjunctival Kaposi’s sarcoma is present frequently in HIV patients and lesions may be mistaken with other conjunctival lesions. Nepal J Ophthalmol 2013; 5(10): 265-267 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8741